Study On The Significance Of Jo:Sag: A Traditional Honorary Cuisine Of The Mising Tribe (International Journal of Food and Nutritional Sciences, 2022)
Food is an important marker of the cultural practices of a particular tribal community. Food habit depicts the cultural ethos and the availability of the ingredients of a particular recipe. Cultural practices and livelihood of particular tribe revolves around the extraction of different resources for their daily usage and tribal communities depends on the natural environment in varied activities. Besides agriculture, livestock rearing is an important livelihood option for the people in the community. These animals serves as additional income to meet the day-to-day cash requirement as well as offering during various ritual practices. The meat (pork, Chicken etc.) and fish cuisine are intricate part of the dishes prepared by the tribe. Mising tribe prepares variety of Meat and Fishes dishes during different cultural and ritual practices. However, meat especially pork serves as the major ingredients on special occasion. One such dish is Jo:sag which is specially prepared in honorary cuisine among the tribe. This dish is prepared either with meat (pork, Chicken) or Fish on various occasion.